Integrating Sustainable Business Through The Implementation of Environment, Social, and Governance (ESG) in Accelerating the Realization of a Green Economy - Anggit Dyah Kusumastuti; Destina Paningrum; Locita Dara Rasendriya (Yayasan Darussalam Bengkulu, 2026)
Background: In facing increasingly complex global challenges, the integration of Environment, Social, and Governance (ESG) and sustainable business plays an important role as a strategic approach not only to generate profits but also as a force to create sustainable positive impact. This research aims to determine the influence of ESG disclosure on the Green Economy with Sustainable Business as a moderating variable. Method: This study employs a descriptive research design with a quantitative approach. Operational measurement of variables is carried out through data on environmental, economic, and social aspects. Secondary data is sourced from BPS (Central Bureau of Statistics) data and the Annual Report of the Ministry of Environment and Forestry (KLHK). Data analysis utilizes Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 4.0 software. Results: The results show that the disclosure of environmental and social aspects has a positive and significant impact on the realization of a green economy. Meanwhile, the disclosure of governance does not have a positive and significant impact on the green economy. Additionally, Sustainable Business strengthens the influence of Environment, Social, and Governance on the green economy. The R Square value indicates that the dependent variable (Green Economy) is 0.605, meaning that approximately 60.5% of the variability can be explained by the independent variables. Conclusion: The disclosure of environment and social aspects has a positive and significant effect on the realization of the green economy, while the disclosure of governance does not have a significant effect. Positive information about ESG practices sends good signals to investors about long-term prospects and commitment to sustainability.